2012
DOI: 10.4097/kjae.2012.62.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warmed ropivacaine solution on onset and duration of axillary block

Abstract: BackgroundBicarbonate, as an adjunct increasing the non-ionized form of local anesthetics, can reduce latency and prolong duration of regional nerve block. Warming of local anesthetics decreases pKa and also increases the non-ionized form of local anesthetics. We warmed ropivacaine to body temperature (37℃) and evaluated the sensory block onset time, motor block onset time and analgesic duration of axillary block.MethodsPatients were consecutively allocated to two groups of 22 patients each. Ropivacaine 150 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Patients were classified according to the Hollman scale (Grade 1 = Full sensation; Grade 2 = Weak sensation; Grade 3 = Recognized as light touch; Grade 4 = Loss of sensation). 22 For the sensory assessment, the tip of the needle (22 Gauge short bevel) was applied to the skin with a force that was adequate to indent the skin but not enough to puncture it, in order to produce a consistent painful sensation when applied to the areas with normal sensation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were classified according to the Hollman scale (Grade 1 = Full sensation; Grade 2 = Weak sensation; Grade 3 = Recognized as light touch; Grade 4 = Loss of sensation). 22 For the sensory assessment, the tip of the needle (22 Gauge short bevel) was applied to the skin with a force that was adequate to indent the skin but not enough to puncture it, in order to produce a consistent painful sensation when applied to the areas with normal sensation.…”
Section: Methodsmentioning
confidence: 99%
“…Time to motor block regression (duration of motor block), defined as the time between complete block (score 2) after local anesthetic injection (T0) and no motor block (score 0) on the modified Bromage scale was evaluated. 22 Motor block was assessed before and 10, 15, and 20 minutes after T0, and thereafter, every 30 minutes during surgery, and every hour in the postoperative period until its complete regression. Pharmacological therapy was based on patient response.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, in addition to that, several studies have investigated if modifying the temperature of applied LAs can have an impact on the onset time of anesthesia. Of six studies published between 1987 and 2019 for various blocks and with different substances, four reported a shortened onset time after injection of pre-warmed LAs ( Mehta et al, 1987 ; Heath et al, 1990 ; Lim et al, 1992 ; Lee et al, 2012 ) and only one study reported no effect on onset time ( Chilvers, 2019 ).…”
Section: Clinical Perspectives and Future Directionsmentioning
confidence: 99%
“…The onset of sensory and motor block was evaluated every 5 minutes for 20 minutes by Hollmen scale 6 for sensory effect and modified Bromage scale 7 for motor effect, until the block was finally established. The duration of sensory block was taken as time elapsed between injection of drug and return of pinprick sensation.…”
Section: Introductionmentioning
confidence: 99%